Mechanisms behind Functional Avidity Maturation in T Cells - Marina Rode von Essen; Martin Kongsbak; Carsten Geisler (Clinical and Developmental Immunology, 2012)
During an immune response antigen-primed B-cells increase their antigen responsiveness by affinity maturation mediated by somatic hypermutation of the genes encoding the antigen-specific B-cell receptor (BCR) and by selection of higher-affinity B cell clones. Unlike the BCR, the T-cell receptor (TCR) cannot undergo affinity maturation. Nevertheless, antigen-primed T cells significantly increase their antigen responsiveness compared to antigen-inexperienced (naïve) T cells in a process called functional avidity maturation. This paper covers studies that describe differences in T-cell antigen responsiveness during T-cell differentiation along with examples of the mechanisms behind functional avidity maturation in T cells.